Role of GABRD Gene Methylation in the Nucleus Accumbens in Heroin-Seeking Behavior in Rats - Hong, Qingxiao; Xu, Wenjin; Lin, Zi; Liu, Jing; Chen, Weisheng; Zhu, Huaqiang; Lai, Miaojun; Zhuang, Dingding; Xu, Zemin; Fu, Dan; Zhou, Wenhua; Liu, Huifen (Frontiers in Pharmacology, 2021)
Epigenetic modifications such as DNA methylation are important regulators of gene expression and may contribute to neuroplasticity and drug-induced aberrant behaviors. Although several brain regions and molecular mechanisms were found to be involved in these processes, relatively little is known about the effects of DNA methylation on heroin-seeking behavior. Using a Sprague-Dawley rat model, we show that heroin self-administration resulted in gamma-aminobutyric acid type A receptor subunit delta (GABRD) gene hypomethylation, which was associated with transcriptional upregulation of GABRD in the nucleus accumbens (NAc). Systemic L-methionine (MET) administration significantly enhanced the reinstatement of heroin-seeking behavior induced by heroin priming, whereas intra-NAc injections of the DNA methyltransferase (DNMT) inhibitor 5′-aza-2′-deoxycytidine (5-Aza-dC) had the opposite effect on heroin-seeking. Meanwhile, 5-Aza-dC treatment decreased DNA methylation and upregulated the expression of GABRD in the NAc, whereas MET had the opposite effect. Our results also suggest that 5-Aza-dC might alter the methylation landscape of the GABRD gene by directly repressing DNMT1 and DNMT3A expression. Furthermore, reinstatement of heroin-seeking behavior was significantly inhibited by directly overexpressing GABRD and remarkably reinforced by GABRD gene silencing in the NAc. Collectively, these results suggest that targeting the GABRD gene and its methylation might represent a novel pharmacological strategy for treating heroin addiction and relapse.